Perovskite topological exciton-polariton disclination laser at room temperature - Feng Jin; Subhaskar Mandal; Xutong Wang; Baile Zhang; Rui Su (Nature Communications)
Abstract Topologically nontrivial systems can be protected by band topology in momentum space, as seen in topological insulators and semimetals, or real-space topology, such as in lattice deformations known as topological disclinations (TDs). TDs, with inherent chiral symmetry, can support localized states pinned spectrally to the middle of the topological gap, preventing hybridization with bulk bands, and making them promising for topological lasers. Here, we experimentally realize a $${C}_{4v}$$ C 4 v symmetric TD laser based on perovskite exciton-polariton lattices at room temperature. Protected by the chiral and point group symmetries of the lattice, the TD state emerges in the middle of the gap and at the core of the perovskite lattice. Under a non-resonant pulsed excitation, coherent polariton lasing occurs precisely at the TD state with a low threshold of 9.5 μJ/cm2, as confirmed by momentum space and real space spectra measurements. This study not only introduces a class of symmetry-protected topological lasers, but also expands the landscape for exploring exciton-polariton light-matter interactions with novel topological structures.